Associations between social support and help-seeking intention regarding music performance anxiety among Chinese music students: mediation via resilience and self-compassion - Sun, Jian; Zhong, Lijuan; Zhou, Xuan; Li, Zhan; Liu, Qian; Liu, Yanchang (Frontiers in Psychology, 2026)
IntroductionMusic performance anxiety (MPA) is a common challenge in higher music education, often undermining students’ confidence, performance quality, and mental health. However, research on help-seeking related to MPA among music students remains limited. Social support is known to buffer stress and promote help-seeking, while self-compassion and resilience may serve as key psychological mechanisms linking social support to help-seeking intentions. This study examined how social support relates to both formal and informal help-seeking intentions regarding MPA among Chinese music students, focusing on the mediating roles of self-compassion and resilience.MethodsA cross-sectional online survey was conducted in March 2025 among 684 students from Sichuan, China. Validated scales measured social support, self-compassion, resilience, and help-seeking intentions. Mediation analyses were performed using structural equation modeling.ResultsThe present study found that social support was not directly related to formal help-seeking intention, but its indirect effects through resilience and self-compassion were significant, indicating full mediation. For informal help-seeking, social support had both direct and indirect effects via resilience and self-compassion, suggesting partial mediation.DiscussionThe findings indicate that social support facilitates help-seeking through both self-compassion and resilience. Strengthening peer and teacher support systems, incorporating self-compassion and resilience training into performance pedagogy, may enhance students’ readiness to seek help. Future longitudinal research should verify these pathways and examine actual help-seeking behaviors.